2019
DOI: 10.1016/j.gca.2019.03.038
|View full text |Cite
|
Sign up to set email alerts
|

Distinct basin-scale-distributions of aluminum, manganese, cobalt, and lead in the North Pacific Ocean

Abstract: Aluminum (Al), manganese (Mn), cobalt (Co), and lead (Pb) are key trace elements in seawater and thus significant in chemical oceanography research. However, although all of these elements are highly scavenged in the ocean, only a few studies focus on the intercomparison of their distributions. Here, we report the basin-scale and full-depth sectional distributions of these elements observed during three GEOTRACES Japan cruises in the North Pacific. We confirmed that a surface maximum of the dissolved (d) speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
60
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(72 citation statements)
references
References 100 publications
(128 reference statements)
10
60
2
Order By: Relevance
“…Another set of concurrently collected samples were analyzed in 2016-2017 (USM) for dissolved La, Ce, and Pr, as part of the entire suite of rare earth elements. A 14-mL aliquot of sample (Boyle et al, 2005), Boyle MP5 = station ALOHA, 1 July 2002 (Boyle et al, 2005) (Zheng et al, 2019). dCe -IOC2002 Stn 9 = this study, Frollje 24-February-11 = station ALOHA (Fröllje et al, 2016), Frollje 21-July-12 = station ALOHA (Fröllje et al, 2016), Frollje 27-Aug-12 = station ALOHA (Fröllje et al, 2016), Frollje 1-June-13 = station ALOHA (Fröllje et al, 2016), de Baar VERTEX IV = 28…”
Section: Dissolved Rare Earth Elements (Rees)mentioning
confidence: 94%
See 1 more Smart Citation
“…Another set of concurrently collected samples were analyzed in 2016-2017 (USM) for dissolved La, Ce, and Pr, as part of the entire suite of rare earth elements. A 14-mL aliquot of sample (Boyle et al, 2005), Boyle MP5 = station ALOHA, 1 July 2002 (Boyle et al, 2005) (Zheng et al, 2019). dCe -IOC2002 Stn 9 = this study, Frollje 24-February-11 = station ALOHA (Fröllje et al, 2016), Frollje 21-July-12 = station ALOHA (Fröllje et al, 2016), Frollje 27-Aug-12 = station ALOHA (Fröllje et al, 2016), Frollje 1-June-13 = station ALOHA (Fröllje et al, 2016), de Baar VERTEX IV = 28…”
Section: Dissolved Rare Earth Elements (Rees)mentioning
confidence: 94%
“…Nishioka et al (2007) suggested that material in the western North Pacific could be swept even further into the open ocean by currents circulating in this region. A recent study of three Japanese GEOTRACES cruises established the importance of margin inputs and basin-wide intermediate water masses in the distributions of dissolved Mn and Co (Zheng et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…(Left) dissolved Mn depth profiles from KM1513 (July 2015) shown with the mean (long dash) and fifth and 95th percentile values (short dash) of numerous dMn measurements made at Station ALOHA (Boyle et al, 2005; Chen & Wu, 2019; Morton et al, 2019) as well as several other stations in the regional North Pacific including the VERTEX‐IV (July 1983), SAFe (May 2009) and KH05‐2‐9 and KH05‐2‐8 (April 2005) (Zheng et al, 2019). Additional station locations mentioned in the text for other elements are also plotted in the map on the right.…”
Section: Resultsmentioning
confidence: 99%
“…Note the KM1513 sample from 180 m appeared contaminated for Fe (0.758 nmol/kg) and is not plotted. (Zheng et al, 2019). Additional station locations mentioned in the text for other elements are also plotted in the map on the right.…”
Section: Vertical Trace Element Profilesmentioning
confidence: 99%
See 1 more Smart Citation